Traditional uses of family Asteraceae in Ethiopia: A review of ethnobotanical knowledge and therapeutic applications - Awoke, Ashebir; Tahir, Muhidin (Ethnobotany Research and Applications, 2025)
Background: The Asteraceae family is one of the most widely used medicinal plant families in Ethiopia, playing a crucial role in traditional healthcare across diverse ethnic and ecological settings. Despite its importance, a comprehensive synthesis of ethnobotanical knowledge, phytochemical constituents, and therapeutic applications remains limited. Methods: A systematic review was conducted by searching multiple electronic databases for studies reporting on the medicinal use of Asteraceae species in Ethiopia. After screening and eligibility assessment, 40 relevant studies (35 published and 5 unpublished) were included. Data on species diversity, plant habits, and parts used, preparation methods, modes of administration, phytochemical profiles, and antibacterial activities were extracted and analyzed. Results: Fifty-six Asteraceae species from 34 genera were documented, predominantly herbs (73.2%), with Vernonia amygdalina Delile and Artemisia abyssinica Sch.Bip. ex Oliv. & Hiern being the most frequently cited. Leaves were the most commonly used plant parts (71.4%). Preparation methods mainly involved crushing fresh material (50%), and remedies were applied dermally, orally, and nasally. Phytochemical analyses identified flavonoids, alkaloids, tannins, and terpenoids, correlating with broad-spectrum antibacterial activity against pathogens such as Staphylococcus aureus and Escherichia coli. However, limited data on dosage, toxicity, and conservation challenges were noted. Conclusions: Ethiopian Asteraceae plants represent a rich resource for traditional medicine and potential drug discovery. Future research should prioritize standardization of preparation, in vivo validation, toxicity studies, and sustainable harvesting practices. Strengthening interdisciplinary collaboration and community awareness is essential for preserving this invaluable ethnobotanical heritage. Keywords: Asteraceae, Antibacterial activity, Ethiopia, ethnobotany, medicinal plants, phytochemicals, traditional medicine